MANAJEMEN KONFLIK UNTUK KEBERHASILAN ORGANISASI: STRATEGI DAN TANTANGAN - Kasmawanto, Zuli; Ni'mah, Khoirotun (LPPM UNISDA, 2025)
This study aims to analyze the impact of conflict, effective conflict management strategies, and challenges in its implementation in the Pucangro Village IPNU organization. This study uses a qualitative method with a case study approach. Data was collected through in-depth interviews with administrators and members of the organization, direct observation of organizational activities, and analysis of internal documents. Conflicts in organizations have positive impacts such as encouraging innovation and strengthening relationships between members, but they can also reduce productivity and performance if not managed properly. This study found that open communication strategies, mediation, collaboration, and conflict management training are effective approaches in resolving conflicts. However, the implementation of these strategies faces challenges such as members' lack of understanding of conflict management, misalignment of the strategy with the local cultural context, communication barriers, lack of resource support, and the dominance of individual leadership. This study suggests strengthening training, internal communication, and inclusive leadership to optimize conflict management in community-based organizations. These findings make practical and theoretical contributions to conflict management in organizations.English translation.